2002
DOI: 10.1046/j.1439-0450.2002.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Entropion, Corneal Ulcer and Corneal Haemorrhages in a One‐Humped Camel (Camelus dromedarius)

Abstract: An unusual case of entropion, corneal ulcer and corneal haemorrhages in a one-humped camel (Camelus dromedaries) is described. The most prominent clinical findings were entropion of both eyelids, severe blephrospasm, epiphora, conjunctivitis, conjunctival oedema, mucopurulent conjunctival discharges, hyperaemia, lacrimation and photophobia. Corneal ulcers and corneal haemorrhages were also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Corneal papilloma, 3 entropion, and corneal ulcer have also been studied in one humped camel. 4 Finally, recently swelling characteristics of fresh camel and bovine cornea in sodium salt solutions were reported by Almubrad et al (2010). 5 The authors observed that initial swelling in both camel and bovine stroma is faster and more prominent compared with later swelling.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Corneal papilloma, 3 entropion, and corneal ulcer have also been studied in one humped camel. 4 Finally, recently swelling characteristics of fresh camel and bovine cornea in sodium salt solutions were reported by Almubrad et al (2010). 5 The authors observed that initial swelling in both camel and bovine stroma is faster and more prominent compared with later swelling.…”
Section: Introductionmentioning
confidence: 95%
“…It was noted that 13 months post removal of corneal dermoids, glaucoma occurred, and corneal fibrosis and cataract were observed. Corneal papilloma, 3 entropion, and corneal ulcer have also been studied in one humped camel 4 . Finally, recently swelling characteristics of fresh camel and bovine cornea in sodium salt solutions were reported by Almubrad et al.…”
Section: Introductionmentioning
confidence: 97%
“…These unusual features motivated the authors to test tear production in the dromedary camel and compare the results with those recorded in other animals. Because there is very little work published on ocular diseases and ophthalmic diagnostic tests in the dromedary camel information on normal ranges, repeatability of the STT is important for this species …”
Section: Introductionmentioning
confidence: 99%
“…Entropion, an inward turning of the eyelid margin, is a common problem in certain purebred dogs 1–3 and has been reported in numerous other domestic species, including cats, 4,5 horses, 6,7 cattle, 8,9 sheep, 10,11 pigs, 12,13 rabbits, 14 and a camel 15 . Of the porcine species, Vietnamese potbellied pigs appear predisposed to entropion due to their relatively enophthalmic globes, predilection for obesity and heavy upper eyelid and forehead brow 13 .…”
Section: Introductionmentioning
confidence: 99%